Participatory agricultural development in practice - Isgren, Ellinor (2012)
Participatory development seeks to actively engage local people and communities in development efforts, from problem identification to evaluation. The concept is, however, vaguely defined and can in reality manifest itself in many different ways, with varying success in creating a sustained impact. There are also a wide range of challenges involved due to the collaborative nature of the approach. This thesis is a qualitative case study exploring the Nnindye project, a participatory agricultural development project that is being carried out in Uganda. The overarching aim is to explore the challenges involved in implementing the Nnindye project which can affect its capacity to generate sustained agricultural development, and what lessons can be learned that might be applicable to future projects in similar settings. To help answer this question, research questions were developed focusing particularly on 1) the kind of participation the project enables, 2) emerging issues that are important to address, 3) the relationship between farmers and “outsiders” involved, 4) gender dimensions and 5) reasons not to participate. Literature from the fields of participatory development and research, particularly experiences from Uganda, helped guide the development of these research questions. To address these research questions, semi-structured interviews were carried out with 80 farmers in Nnindye parish (both participants and non-participants), sampled through a non-probability sampling method. Additionally, 5 agricultural researchers familiar with using farmer participatory approaches in other projects in Uganda were sampled through convenience sampling, and their experiences and views were explored through semi-structured interviews. At the end of the study, a final interview was carried out with one of the Nnindye project implementers. As it turns out, participation in the project cannot be categorized. Respondents mainly identified material benefits but also learning and other less tangible benefits. One's contribution was most often seen as practical input, usually labor. Influence in the project was similarly commonly perceived in practical terms rather than “political”. This material or pragmatic nature of participation seen among some participants may suggest that more efforts are needed to strengthen the learning process and community building capacity, but also tangible benefits can be of great value in both short and long term. Luckily, one doesn't have to exclude the other. Participant ownership of the process is something that is viewed by the project implementors as central, and participants on numerous occasions expressed negative opinions towards past topdown approaches. However, “ownership” must not mean lack of support. Dissatisfaction with the group leadership and unfair distribution of benefits among the project members was discovered and there is a need for more systematic monitoring and facilitation. The results overall show an overwhelmingly positive attitude towards scientists and extension staff among the farmers, who stated that they view these as very knowledgeable. This seemingly positive relationship is an asset but it must be remembered that it is not static – negative experiences can jeopardize both the current project and attitudes towards collaborative efforts and development in general. Gender dimensions are important to consider in practically all aspects of a project, and gender awareness is required among the implementers to ensure that the project benefits women and men alike. In general, parallels could be drawn from the Nnindye project to the experiences of the researchers, speaking for the usefulness of these findings to other academics and development practitioners.